2016
DOI: 10.1073/pnas.1612579113
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle progression inCaulobacterrequires a nucleoid-associated protein with high AT sequence recognition

Abstract: Faithful cell cycle progression in the dimorphic bacterium Caulobacter crescentus requires spatiotemporal regulation of gene expression and cell pole differentiation. We discovered an essential DNA-associated protein, GapR, that is required for Caulobacter growth and asymmetric division. GapR interacts with adenine and thymine (AT)-rich chromosomal loci, associates with the promoter regions of cell cycle-regulated genes, and shares hundreds of recognition sites in common with known master regulators of cell cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(50 citation statements)
references
References 95 publications
1
48
0
1
Order By: Relevance
“…Collectively, our data suggest that GapR and, by extension, the conserved domain DUF2312 encode a NAP function critical for cellular replication. While this manuscript was under revision, the Shapiro group published an article describing the identification of the same nucleoid‐associated protein in C. crescentus (Ricci et al , ). The only overlap with our study is the DNA‐binding preference of the protein to AT‐rich DNA sequences and its essential function in cell cycle progression under standard laboratory conditions (nutrient‐rich PYE medium, 30°C).…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, our data suggest that GapR and, by extension, the conserved domain DUF2312 encode a NAP function critical for cellular replication. While this manuscript was under revision, the Shapiro group published an article describing the identification of the same nucleoid‐associated protein in C. crescentus (Ricci et al , ). The only overlap with our study is the DNA‐binding preference of the protein to AT‐rich DNA sequences and its essential function in cell cycle progression under standard laboratory conditions (nutrient‐rich PYE medium, 30°C).…”
Section: Discussionmentioning
confidence: 99%
“…Most of these CSPs were of unknown function at the time they were first characterized, although further studies have shown them to be highly reliable molecular markers for these groups, and biochemical studies on them are leading to discovery of novel and important functions that were hitherto unrecognized [16][17][18][19][20]. Thus, not knowing the function of a conserved protein that is uniquely shared by a given group of species should not be a cause for criticism.…”
Section: Genomic Evidence For the Cohesiveness Of The Family Borreliamentioning
confidence: 99%
“…S6). It has been shown that many nucleoid-associated proteins from C. crescentus, such as HU or GapR, are enriched in AT-rich chromosomal regions (39)(40)(41). Furthermore, AT-rich sequences are typically found at transcriptional promoters, which are heavily occupied by RNA polymerase or regulatory proteins.…”
Section: Mipz Binds Dna In a Sequence-independent Manner In Vivomentioning
confidence: 99%